2015
DOI: 10.1080/87568225.2015.973821
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the CCAPS, CAS, and OQ-45

Abstract: This article reports on a study evaluating the clinical utility of three clinical assessment measures commonly used in university counseling centers: the Outcome Questionnaire-45 (OQ-45), the Counseling Center Assessment of Psychological Symptoms, and the College Adjustment Scales. Results found subscales assessing depression and anxiety were highly correlated between measures; however, subscales assessing academic and family difficulties correlated only slightly. Clinicians ranked the OQ-45 significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Several studies have reported the utility of the CCAPS‐62 for university students in the United States (McAleavey et al, ; Nordberg, Castonguay, McAleavey, Locke, & Hayes, ). According to MacFarlane, Henry, Nash, Kissel, and Bush's () empirical study, the CCAPS‐62 was more informative when forming initial diagnostic impressions than the Outcome Questionnaire‐45 (Lambert et al, ) and College Adjustment Scale (Anton & Reed, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the utility of the CCAPS‐62 for university students in the United States (McAleavey et al, ; Nordberg, Castonguay, McAleavey, Locke, & Hayes, ). According to MacFarlane, Henry, Nash, Kissel, and Bush's () empirical study, the CCAPS‐62 was more informative when forming initial diagnostic impressions than the Outcome Questionnaire‐45 (Lambert et al, ) and College Adjustment Scale (Anton & Reed, ).…”
Section: Introductionmentioning
confidence: 99%
“…Examining the predictive validity of the Academic Distress subscale for relevant academic outcomes will provide a basis for its meaningful, accurate, and reliable interpretation. MacFarlane et al's (2015) comparison of three symptom inventories at a college counseling center generated uncertainty about the predictive validity of the Academic Distress subscale. They found that the Academic Distress subscale had only a small (.21) correlation with the Academic Problems subscale of the College Adjustment Scales (CAS), and a much stronger (.71) correlation with the Family Problems subscale of the CAS.…”
mentioning
confidence: 99%
“…In a university counseling center, MacFarlane et al. () assessed correspondence between clinicians’ diagnostic impressions and results obtained from assessment measures and found that clinicians ranked the OQ‐45 the lowest in terms of correspondence with their diagnostic impressions than all other measures assessed.…”
mentioning
confidence: 99%
“…Third, the OQ may be invalid in some diagnostic groups and treatment settings. Previous authors have expressed concerns that the OQ did not accurately measure distress in their patient populations, including somatoform disorders, psychotic disorders, and substance use disorders (Conijn, Emons, De Jong, & Sijtsma, 2015;MacFarlane, Henry, Nash, Kissel, & Bush, 2015). In an inpatient setting, Doerfler, Addis, and Moran (2002) found that those diagnosed with major depressive disorder scored higher on the SD subscale of the OQ-45 than those with schizophrenia and other severe mental illnesses (e.g., bipolar disorder).…”
mentioning
confidence: 99%
See 1 more Smart Citation